(untitled) (Research, Society and Development, 2021)
Diamondback moth represents one of the major Brassicaceae plagues and the main current control method relies on the agrotoxins use. The search for alternative phytosanitary control methods demonstrates that the vegetal extracts have broadly studied and now represent a relevant option to control insects-plagues in small cultivation areas. Was evaluated the effect of the aqueous extract Tradescantia pallida 10% in oviposition and the feeding preference of Plutella xylostella, in laboratory conditions. That plant does not present herbivory reports, which raises the hypothesis of representing an efficient control alternative. P. xylostella couples introduced in experimentation cages for 10 days, to assess the activity of oviposition, being exposed to the botanic extract in the feeding and the oviposition substrate, with the eggs average number per day and fertility being assessed. To assess feeding, two tests developed: free choice and no choice of food source during 48 hours of evaluation. The results indicate that the aqueous T. pallida extract changes the oviposition activity of P. xylostella, reducing the average number of eggs per day and the fertility. It was also possible to observe the non-preference, regarding feeding, for substrates that were treated with the extract. The results observed in the study can contribute to amplify the small producers decision-making processes and the involved sectors regarding the choice of supplies that respect environmental and human health.